Psychological well-being among mothers of children with autism spectrum disorder: The role of family function - Dinie Ratri Desiningrum; Dewi Retno Suminar; Endang Retno Surjaningrum (Universitas Ahmad Dahlan, 2019)
The mother of children with autism is the most vulnerable person to have stress and depression. Therefore they need positive psychological well-being to optimize the caring of children. Family is the primary environment in supporting the mother's mental health. This study aimed to find out how family functions correlate with psychological well-being among the mother of a child with autism. A quantitative approach was applied, involving 142 mothers who had autistic children selected through purposive sampling techniques. The data was collected using Family Functioning and Psychological Well-being instruments. The data was then analyzed with regression analysis. The results show that family functioning and psychological well-being are correlated significantly. The more effective family function based on the perception of the mother, the higher the psychological well-being of the mother, and vice versa. Problem-solving, communication, affective response, and role are dimensions that influence psychological well-being, while behavior control and affection dimensions are not significant. The results of the study can provide input suggestions for the government, such as through family empowerment regarding the importance of supporting and optimizing the role of family members to stimulate the psychological well-being of mothers of children with an autism spectrum disorder.